PRINCIPAIS COMPLICAÇÕES NA SALA DE RECUPERAÇÃO PÓS-ANESTÉSICA DO HOSPITAL UNIVERSITÁRIO DE DOURADOS - PEREIRA, Gabriela Duarte; WATANABE, Elaine Aparecida Mye Takamatu; BERGAMASCHI, Fabiana Perez Rodrigues; GANASSIN, Fabiane Melo Heinen (ANAIS DO ENIC, 2017)
-